Side effects from epidural analgesia in laboring women and risk of cesarean deliveryAJOG Global Reports at a Glance - Alessandro Ghidini, MD; Kelly Vanasche, BSN; Alyssa Cacace, BS; Marietta Cacace, BSN; Simona Fumagalli, RM; Anna Locatelli, MD (Elsevier, 2024)
BACKGROUND: Epidural analgesia may cause maternal hypotension and changes in the fetal heart rate. The implications of such side effects on the course of labor and delivery are incompletely understood. OBJECTIVE: This study aimed to assess whether the occurrence of maternal or fetal side effects associated with labor epidural analgesia increased the risk for cesarean delivery. STUDY DESIGN: This was a cohort study of all women who underwent epidural analgesia during labor for the period October 1, 2020 to December 31, 2020. Excluded were cases of multiples, fetal death, noncephalic presentation, and gestational age at birth <37.0 weeks. Maternal vital signs and fetal heart rate tracings for the 1 hour before and 1 hour after epidural analgesia was administered were reviewed. The occurrence of maternal hypotension, defined as a continuous variable and dichotomized into a decrease in maternal systolic blood pressure to <90 mm Hg or a drop in systolic blood pressure by >20% below the last value before epidural analgesia was administered, was related to changes in the fetal heart rate category. The principal outcome was cesarean delivery rate; binary logistic regression analysis was used to control for confounders, and mediation model analysis was used to quantify the extent to which significant variables participated in the causation pathway to cesarean delivery (SPSS version 28 was used for the analyses). RESULTS: A total of 439 women met the study criteria. Significant adverse reactions owing to epidural occurred in 184 of 439 women (41.9%) and included severe maternal hypotension in 159 of 439 participants (36.2%) and worsening fetal heart rate category in 50 of 439 participants (11.4%). The logistic regression analysis revealed that cervical dilation at epidural (P=.03), the duration of labor after epidural (P<.001), and worsening fetal heart rate category within 60 minutes of epidural administration (P=.01) were independently associated with recourse to cesarean delivery. The mediation analysis showed that both cervical dilatation at epidural administration and worsening fetal heart rate category had significant direct and indirect effects in the pathway to cesarean delivery. CONCLUSION: Worsening fetal heart rate category related to labor epidural independently increased the risk for cesarean delivery.